IMPROVING YEAR IX STUDENTS’ ACHIEVEMENT OF MAN 1 WEST ACEH IN LEARNING PHYSICS THROUGH PROJECT BASED LEARNING MODEL - Risna Dewi (FKIP Universitas Al Washliyah Medan, 2023)
This study aimed to: 1) determine whether there was an increase in physics learning outcomes at MAN 1 West Aceh using the PjBL learning model. This type of research was a classroom action research (CAR) which were carried out in 2 cycles in which in each cycle consisted of 4 stages, namely: the Planning, Action, Observation, and Reflection stages.The research instrument was validated by physics experts and teachers. The questions were tested for initial feasibility and then tested to Year XI. MIA 1 West Aceh for the 2022-2023 academic year to collect research data. Data were analyzed by qualitative and quantitative methods. The results of the research were 1) the application of the PjBL learning model to mechanical wave material can improve physics learning outcomes, the magnitude of the increase in physics learning outcomes on average before action was 57.6, the first cycle with an average of 67.3 and the second cycle, it reached an average of 83.8. In cycle I, the average value of mechanical wave material was 85.6 in the good category and cycle II the average value of mechanical wave material was 88.7 in the very good category.